Fenomena Persekusi Ekspresi Beragama dalam Perspektif Pendidikan Kristen - Anjaya, Carolina Etnasari (Sekolah Tinggi Teologi Kanaan Nusantara, 2021)
Evangelism organized by believers in virtual social spaces has led to many reports of alleged blasphemy. This gives rise to a sense of persecution in religious expression for believers. This feeling is based on the existence of unbalanced conditions or the dominance of the majority in the freedom of expression of religious people in Indonesia. This article has a purpose, namely to provide an understanding of the main principles in evangelism and what reflections can be made from them. The method uses descriptive qualitative with literature study. Some of the principles contained include: First, the principle of evangelism cannot be separated from the teaching or education process. Second, the principle of exemplary delivery of God's word. Third, the principle of awareness and sincerity wholeheartedly. Fourth, the principle of lifelong education. Facing the phenomenon of religious expression in virtual media, there are four main things that need to be examined in depth, namely: one, whether the purpose of evangelism is truly sincere for the glory of God. Two, whether the content of the preaching is really the pure gospel. Three, whether the method or method of delivering the gospel is in accordance with the values of the Christian faith. Fourth, whether the person who conveys the word has lived his word. These four things become an absolute reflection in the organization of evangelism.AbstrakPenginjilan yang diselenggarakan umat percaya pada ruang sosial virtual menimbulkan banyak pelaporan dugaan penistaan agama. Hal ini memunculkan rasa adanya persekusi dalam ekspresi beragama bagi orang percaya. Rasa tersebut dilandasi oleh adanya kondisi yang tidak berimbang atau dominasi mayoritas dalam kebebasan berekspresi umat beragama di Indonesia. Artikel ini memiliki sebuah tujuan yaitu memberikan pemahaman prinsip utama dalam penginjilan dan refleksi apa yang dapat dibangun darinya. Metode mempergunakan deskriptif kualitatif dengan studi literatur. Beberapa prinsip yang terkandung antara lain: Pertama, prinsip penginjilan tidak dapat dilepaskan dari proses pengajaran atau pendidikan. Kedua, prinsip keteladanan penyampai firman Tuhan. Ketiga, prinsip kesadaran dan kesungguhan sepenuh hati. Keempat, prinsip pendidikan sepanjang hayat. Menghadapi fenomena dalam ekspresi beragama di media virtual, ada empat hal utama yang perlu diperiksa secara mendalam yaitu: satu, apakah tujuan penginjilan benar-benar tulus untuk kemuliaan Tuhan. Dua, apakah konten pemberitaan adalah sungguh Injil yang murni. Tiga, apakah cara atau metode penyampaian Injil sudah sesuai dengan nilai-nilai iman Kristen. Empat, apakah diri penyampai firman sudah menghidupi perkataanya. Keempat hal tersebut menjadi refleksi yang mutlak dalam penyelenggaraan penginjilan.